Personalistyczny model biografii w świetle zagadnienia podmiotowości Biografia, - Anita Całek, Anita Całek (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The article presents a model of personalist biography that stands in opposition to the postmodernist one. The personalist biography model refers in terms of anthropology to Viktor E. Frankl, the founder of logotherapy (‘Third Viennese School of Psychotherapy’) and the key thinkers of the personalist movement: Karol Wojtyła, Mieczysław Krąpiec, Józef Tischner and Czesław S. Bartnik. Stressing the subjective aspect of biography, the personalist model allows for capturing the personal character of the created biographical portrait of a given person while also taking into account the postulates formed by the critics of biographical writing in its traditional and later structuralist forms, especially the postulates related to the requirement of biographer’s objectivity and neutrality. The personalist biography model also takes into consideration the insights of the French theorists on the inevitable involvement of the researcher in the reconstructed picture of a life and the considerations on the character of representation (by F. Ankersmit and M. P. Markowski).